Stability analysis of an eco-epidemiological model incorporating a prey refuge - Pal, A. K. K.; Samanta, G. P. P. (Nonlinear Analysis: Modelling and Control, 2010)
The present paper deals with the problem of a predator-prey model incorporating a prey refuge with disease in the prey-population. We assume the predator population will prefer only infected population for their diet as those are more vulnerable. Dynamical behaviours such as boundedness, permanence, local and global stabilities are addressed. We have also studied the effect of discrete time delay on the model. The length of delay preserving the stability is also estimated. Computer simulations are carried out to illustrate our analytical findings.